2023
DOI: 10.1021/acs.jpcb.3c05598
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced Asymmetric Charge States of Amino Acids in Supramolecular Nanofibers

Y. Li,
M. Kim,
T. H. Pial
et al.

Abstract: Electrostatic interactions contribute critically to the kinetic pathways and thermodynamic outcomes of peptide selfassembly involving one or more than one charged amino acids. While it is well understood in protein folding that those amino acids with acidic/basic side chains could shift their pK a s when placed in a hydrophobic microenvironment, to what extent aggregation of monomeric peptide units from the bulk solution could alter their charged status and how this change in pK a values would reciprocally imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…C 12 is the hydrocarbon hydrophobic core, V (valine) provides hydrogen bonds, hydrophobicity and E (glutamic acid) is negatively charged and hydrophilic. Our previous study shows that only the outer E of the PA is deprotonated or carries −1 e charge 32 in a self-assembled fiber. Keeping this in mind, we also model the inner glutamic acid as protonated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C 12 is the hydrocarbon hydrophobic core, V (valine) provides hydrogen bonds, hydrophobicity and E (glutamic acid) is negatively charged and hydrophilic. Our previous study shows that only the outer E of the PA is deprotonated or carries −1 e charge 32 in a self-assembled fiber. Keeping this in mind, we also model the inner glutamic acid as protonated.…”
Section: Resultsmentioning
confidence: 99%
“…GROMACS 2021.5 42 and MARTINI3 force field 33,43 are combined in the coarse-grained simulations. We used similar definitions of MARTINI3 beads for C12 as defined in our previous work 32 and mapped bond, angle parameters with all-atom simulation (see ESI†). Our previous work showed that Martini 3 would provide a similar fiber structure to CHARRM36 force-field.…”
Section: Methodsmentioning
confidence: 99%
“…However, the highly condensed structures of SPAs involves additional challenges, such as the local p K a , which might differ from that in the bulk solution, leading to variations in the ionization of the amino acids . For instance, glutamic acids were found to be only partially charged at the surface of SPA nanofibers . Addressing these ionization variations requires constant-pH simulations, implemented in GROMACS, , NAMD, and AMBER .…”
Section: Spas At Different Resolutions: From Electrons To Molecular A...mentioning
confidence: 99%
“… 95 For instance, glutamic acids were found to be only partially charged at the surface of SPA nanofibers. 96 Addressing these ionization variations requires constant-pH simulations, implemented in GROMACS, 97 , 98 NAMD, 99 and AMBER. 100 However, given their high computational demand, large systems, such as SPA structures, are still challenging for constant-pH simulations.…”
Section: Spas At Different Resolutions: From Electrons To Molecular A...mentioning
confidence: 99%
“…It is also important to note that the expected pK a of amino acids and prosthetic motifs used to construct all of the MDPs here could shift as a result of their position on the peptide and/or due to aggregation-induced pK a shifts. [30,31] Efforts to quantify pK a values for the various ionizable groups in these peptides via titration did not yield precise measurements and instead suggested a range of charged states, likely due to a broadened charge distribution resulting from peptide assembly.…”
Section: Multidomain Peptide Designmentioning
confidence: 99%